2020
DOI: 10.3389/fnut.2020.00070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Probiotics for Warfighter Health and Performance

Abstract: The probiotic industry continues to grow in both usage and the diversity of products available. Scientific evidence supports clinical use of some probiotic strains for certain gastrointestinal indications. Although much less is known about the impact of probiotics in healthy populations, there is increasing consumer and scientific interest in using probiotics to promote physical and psychological health and performance. Military men and women are a unique healthy population that must maintain physical and psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 140 publications
0
16
0
Order By: Relevance
“…Comprehensive narrative and systematic reviews focused exclusively on probiotic use in athletes have concluded that ∼65% of studies show favorable effects of probiotics on some aspect of immune function in athletes to include reducing the incidence, duration, and/or severity of RTI. 25–27 In one of those reviews, a position stand on probiotic use in athletes, the authors concluded that “specific probiotic strains can reduce the number of episodes, severity and duration of upper RTI” in athletic populations. 26 …”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive narrative and systematic reviews focused exclusively on probiotic use in athletes have concluded that ∼65% of studies show favorable effects of probiotics on some aspect of immune function in athletes to include reducing the incidence, duration, and/or severity of RTI. 25–27 In one of those reviews, a position stand on probiotic use in athletes, the authors concluded that “specific probiotic strains can reduce the number of episodes, severity and duration of upper RTI” in athletic populations. 26 …”
Section: Resultsmentioning
confidence: 99%
“…Despite no research specific to such personnel being identified, several studies reporting on relevant cognitive measures/tasks and their link to the gut microbiota within healthy/unhealthy populations were available for examination. A recently published narrative literature review authored by the US Department of Defense [ 50 ] included the discussion of evidence regarding the physical and/or cognitive benefits of probiotics in healthy adults. Their findings were broadly consistent with this completely independent narrative review.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy young mice without systemic inflammation, probiotic Lactobacillus plantarum supplementation not only improved lean mass but also muscle function (68). A series of recent reviews (74)(75)(76)(77)(78) and original studies (69-73) have investigated the impact of probiotic supplementation on lean mass and physical performance in humans. After probiotic supplementation, some studies in athletes (predominately males) showed improvements in muscle strength, power, and exercise recovery (69-72), but none observed significant alterations in body lean mass (69)(70)(71)(72)(73).…”
Section: Probiotic and The Gut Microbiotamentioning
confidence: 99%